The Relationship Between Destination Experience and Tourists' Intention to Recommend and Revisit - Chou, Mei-Chu; Tsai, Chin-Fa; Leelapattana, Winitra; Thongma, Weerapon (Journal of Ecohumanism, 2025)
Tourism destinations increasingly rely on delivering exceptional experiences to encourage tourist loyalty and stimulate positive behavioral intentions such as repeat visits and word-of-mouth (WOM) recommendations. This review examines the relationship between destination experiences and tourists’ intention to recommend and revisit, drawing from multidisciplinary literature and key theoretical models. It explores the impact of experiential components including service quality, emotional engagement, cultural authenticity, and environmental setting on tourist satisfaction and destination loyalty. The review emphasizes the role of memorable tourism experiences (MTEs), destination image, and emotional bonds in shaping revisit intentions and WOM behavior. It also analyzes the influence of digital communication, particularly electronic word-of-mouth (eWOM), on shaping destination perceptions and decision-making. The paper integrates insights from foundational theories such as the Expectation-Confirmation Model (ECM), Theory of Planned Behavior (TPB), and Expectation-Disconfirmation Theory (EDT) to explain how satisfaction, perceived value, and social influence contribute to loyalty development. In addition, it identifies key push and pull factors affecting destination choice and examines demographic influences on tourist behavior. The study concludes by highlighting strategic implications for destination marketing such as the importance of personalization, reputation management, and sustainability. It identifies future research opportunities in areas like post-pandemic recovery, AI-driven tourism engagement, and evolving tourist motivations. By synthesizing diverse findings, this review comprehensively explains how positive destination experiences drive long-term tourist loyalty and advocacy in a highly competitive global tourism landscape.